Draft Annual Plan 1972-73 Government of Andhra Pradesh - Planning Commission (Planning Commission, 1972)
Agricultural Production, Training centres, Land Development, Minor Irrigation, Soil Conservation, Ayacut Development, Animal Husbandry, Dairying and Milk Supply, Forests, Fisheries, Warehousing and Marketing, Cooperation, Community Development, Irrigation, Power. Large and Medium Industries, Mineral Development, Metric System, Village Small Scale Industries, Handlooms, Roads, Road Transport, Minor Ports, Tourism, General Education, Technical Education.
Government of Andhra Pradesh, Planning and Co-operation Department
Government of Andhra Pradesh, Planning and Co-operation Department